Activities of the Grand Duchy of Lithuania chancellery under the management of Leon Sapieha (1585–1623) - Diemantaitė, Vita (Lietuvos istorijos studijos, 2020)
After the reforms that took place in 1566 the Grand Duchy of Lithuania and the Union of Lublin began its new phase of life in 1569. During this phase The Chancellery of the Grand Duchy of Lithuania played an essential role. At the time the institution was comprised of Chancellor, Vice-Chancellor and its most important employees – clerks – people of average nobility that had a chance to show their knowledge working at a chancellery. Leon Sapiega was one of such people. While examining the works of other historians we can notice that L. Sapiega has a variety of biographies, but not including the clerical aspect, they can be considered to be a collection of chronological presentation of facts and not a comprehensive biography of a high-ranking official. Therefore, the purpose of this article is to answer the question of how L. Sapiega as a person influenced the development of the Chancery of the GDL. Institutions are usually represented by leaders and each leader leaves a footprint in the institution’s history. L. Sapiega was not an exeption as his office had undergone several stages of development.